Faktor-Faktor Yang Mempengaruhi Pengelolaan Dana Desa (Desa Kare, Kecamatan Kare, Kabupaten Madiun) - Nurharibnu Wibisono; Fatchur Rochman; Esa Nurwanti Nurwanti (JAMER : Jurnal Akuntansi Merdeka, 2022)
It research aims to examine the influence of community participation, transparency & accountability in the supervision of dorp funds in Kare Village, Kare District, Madiun Regency. The sample in it research were village officials and RTs. Searching for main data through spread out questionnaires to the study sample. The data obtained were tested with regression of multiple linear studies. Study results show the variable of social participation has no effect on the supervision of village funds, the variable of transparency has an influence on the management of dorp funds, the variable of accountability has an effect on the management of dorp funds and the variables of community participation, transparency and accountability have an influence on the supervision of dorp funds. Adjsted R2 has a mark of 55.1%, which means that the variable of village fund supervision is affected by community participation, transparency and accountability while the rest 44.9% is the influence of other reasons not included in this research.